Le soutien à la parentalité : entre émancipation et contrôle - David Pioli (Sociétés et Jeunesses en Difficulté)
Parental assistance: between emancipation and control            At the end of the 80’s, parenting assistance started getting structured based on administrative networks in charge of managing nursery projects. Today, it is part of the action of public authorities. But parenting assistance follows contradictory logics and therefore does not refer to an univocal frame of reference. On the one hand, the issue is to promote parenting skills so that parents can fulfil their rights and obligations even when they are "failing". Parenting assistance focuses on projects aiming at building around the child and the child’s needs a sense of harmony everyone can benefit from in terms of security and personal development. On the other hand, parenting assistance is linked to a disciplinary view of public action fuelled by insecurity and prevention as well as threat and repression. Parenting action is thus a means of assuring public safety and prevention focuses less on the safety of children than on that of others. Between emancipation and control, the relationship between the private and the public spheres can be viewed in two opposite ways but with the same focus on the child that shows in the repeated assertion that family order is a component of global social order.